Transformational Leadership Styles and Mentoring Functions Towards a Culture of Patient Safety Moderated by Competence of the Nurse - Wahyudyasa, Putu Tara Judica; Hasyim, Hasyim; Kusumapradja, Rokiah (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Patient safety culture is the fundamental in implementing patient safety at hospitals. Every hospital must guarantee the implementation of patient safety in the health services. Objective: The study aimed to examine the effect of transformational leadership style and mentoring function on patient safety culture which is moderated by the competence of nurses in the hospital. Method: This research method was conducted using a quantitative survey with a cross-sectional study approach. A total of 57 samples were involved in this study. The data analysis method used in this study is multiple linear regression analysis. Result: The results of the study show that there is a positive and significant influence of transformational leadership on patient safety culture. The mentoring function has no significant effect on patient safety culture. Nurse competence has not been able to moderate the effect of Transformational Leadership on Patient Safety Culture, and nurse competence has not been able to moderate the influence of the Mentoring Function on Patient Safety Culture. Conclusion: The greatest coefficient value in this study is the effect of transformational leadership on patient safety culture moderated by nurse competence by 45.4%